Neurocognition and Depressive Symptoms have Unique Pathways to Predicting Different Domains of Functioning in Major Depressive Disorder. (April 2023) - Wood-Ross, Chelsea; Tran, Tanya; Milanovic, Melissa; Jokic, Ruzica; Milev, Roumen; Bowie, Christopher R.
Background: Research has established the independent relationships between depressive symptoms to cognition and functioning in depression; however, little is known about the role of mediators in this relationship. We explored the role of neurocognitive abilities, depressive symptom severity, dysfunctional attitudes, and functional capacity in predicting two dimensions of daily functioning in individuals with major depressive disorder (MDD). Methods: One hundred and twenty-four participants (mean age = 46.26, SD = 12.27; 56% female) with a diagnosis of MDD were assessed on a standard neurocognitive battery, self-reported depressive symptoms, dysfunctional attitudes, and clinician-rated functional impairment. They completed a performance-based assessment of functional competence. Results: Confirmatory path analyses were used to model the independent and mediated effects of variables on two domains of functioning: social (relationships and social engagement) and productive (household and community activities). Cognition and depressive symptoms both predicted productive functioning, and dysfunctional attitudes mediated each of these relationships. Functional competence was a significant mediator in the relationship between neurocognition and productive functioning. Depressive symptoms and cognition were direct predictors of social functioning with no significant mediators. Conclusions: There are divergent pathways to different dimensions of daily functioning in MDD. Measurement implications include the consideration of multiple levels of predicting productive activities and more direct relationships with social outcomes. Treatments that directly target depressive symptoms and cognition might not generalize to improvements in everyday functioning if additional pathways to functioning are not addressed.